ANALISIS YURIDIS TERKAIT PENEGAKAN HUKUM TERHADAP TINDAK PIDANA BULLYING MENURUT PASAL 76 C UNDANG-UNDANG PERLINDUNGAN ANAK - Dewi, Caryn Andin Cynthia; Rizky, Haliza Kanaya; Averoezy, Fauzul; Sutrisno, (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
Bullying is a complex and detrimental social phenomenon, frequently occurring in school environments and leading to serious psychological impacts on victims. This research aims to analyze the enforcement of law against bullying under Article 76 C of the Child Protection Act in Indonesia. The method employed is normative legal research, which emphasizes the implementation of legal norms, regulatory frameworks, and relevant legal theories. This study also utilizes a descriptive analytical approach, collecting secondary data from various legal sources, including laws and previous research findings. Findings indicate that despite clear regulations, law enforcement is often impeded by factors related to law enforcement personnel, legal frameworks, resources, society, and culture. The conclusion of this research emphasizes the need for stronger law implementation and societal awareness to prevent bullying. The implications of this research provide a foundation for more effective policy-making for child protection and fair law enforcement.